Enhancing the Legal Framework: Optimizing Zakat as an Income Tax Deduction in Indonesia - Adinugraha, Hendri Hermawan; Surur, Achmad Tubagaus; Achmad, Dliyaudin (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This research aims to comprehensively examine the implementation of zakat policy as a deductible component of taxable income in Indonesia. The study adopts a qualitative approach, utilizing primary sources such as the Qur’an, Hadith, Law No. 23/2011 on Zakat Management, and relevant tax regulations. Data were collected through a literature review and analyzed descriptively to interpret and explain the findings. The study concludes that, under positive law, zakat as a deduction from taxable income is governed by Article 22 of Law No. 23/2011, further reinforced by the Indonesian Ulema Council’s Fatwa No. 3 of 2003 on Zakat on Income/Profession. Zakat payments from official institutions such as BAZNAS can be deducted from taxable income. An example of this implementation is in Aceh Province, as stipulated in Article 192 of Law No. 11/2006 on the Government of Aceh. These findings highlight the potential of the zakat policy to alleviate the double burden faced by Muslim taxpayers while fostering economic redistribution. This research contributes by providing recommendations to strengthen the legal framework and enhance public education to maximize the benefits of zakat policy. Such efforts aim to improve tax compliance and promote social welfare through the synergy between tax and zakat systems.